Rectus abdominis muscle flap for repair of the gastrojejunal leakage after distal gastrectomy with Billroth II anastomosis for gastric cancer - Díaz-Plasencia, Juan A. (2019)
Anastomotic leakages at the gastrojejunostomy site are difficult to repair, due to complex gastrointestinal anatomy. This is thefirst study reporting clinical use of rectus abdominis muscle (RAM) flap for repair of gastrojejunostomy leakage. A patient withleakage of gastrojejunostomy after distal gastrectomy with Billrroth II anastomosis for gastric cancer underwent repair using leftRAM flap, based on superior epigastric artery. Rectus abdominis muscle flap, after being harvested was then anchored to theedges of the leak of gastrojejunostomy with few interrupted 2-0 vicryl sutures. Gastrojejunostomy leak sealed in the two cases.Rectus abdominis muscle flap for closure of gastrointestinal defect is a simple, technically easy and dependable procedure,which can be performed, quickly in critically ill patients. It can be used for repair of a large gastrointestinal defect with friableedges when omentum is not available or when other conventional methods are impractical.